Association of graft survival with tacrolimus exposure and late intra-patient tacrolimus variability in pediatric and young adult renal transplant recipients: an international CTS registry analysis - Gold, Annika; Tönshoff, Burkhard; Döhler, Bernd; Süsal, Caner (Transplant international, 2020)
Adolescent and young adult age is a high-risk window with an alarmingly increased likelihood of premature kidney graft loss due to immunological rejection. Using the large database of the Collaborative Transplant Study, we analyzed whether a more intense and less variable exposure to tacrolimus could counteract this young age-related enhanced immunoreactivity. Kidney graft recipients aged 12-23 years (n = 964) with a 1-year tacrolimus trough level between 4.0 and 10.9 ng/ml had a 5-year graft survival rate of 85.1%, significantly better than the poor 66.1% rate in patients with a trough level below 4.0 ng/ml who showed a 2.38-fold increased risk of graft loss in the multivariable analysis (P < 0.001). This association was not apparent in young children aged 0-11 years (n = 455) and less pronounced in adults aged 24-34 years (n = 1466). However, an intra-patient variability of tacrolimus (IPV) trough level ≥1.5 at post-transplant years 1 and 2 was associated with an increased graft loss risk in both 12- to 23-year-old and 0- to 11-year-old recipients (P < 0.001 and P = 0.045). Patients with high IPV made up as many as 30% of kidney graft recipients, indicating that a more intense and less variable exposure to tacrolimus could improve graft survival strongly in this high-risk group.
First published: 02 September 2020
Gesehen am 13.12.2021